1998
DOI: 10.1002/(sici)1097-4679(199812)54:8<1063::aid-jclp6>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

The reasons for living inventory for adolescents (RFL-A): Development and psychometric properties

Abstract: The role of adaptive beliefs and attitudes against suicide has not been given adequate attention in the clinical or assessment literature. This article reports on the development and initial psychometric properties of a 32-item self-report inventory, the Reasons for Living Inventory for Adolescents (RFL-A). In Phase 1, we used exploratory and confirmatory factor analyses to identify five correlated factors: Future Optimism, Suicide-Related Concerns, Family Alliance, Peer Acceptance and Support, and Self-Accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
84
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 21 publications
9
84
0
Order By: Relevance
“…30,31 For those 18 years and older vs those younger than 18 years, impulsivity was assessed with the Barratt Impulsivity Scale or the impulsivity subscale of the Conners’ Teacher Rating Scale, 32,33 negative life events in the previous 12 months were assessed with the shortened version of the Social Readjustment Rating Scale or the Life Events Checklist, 34,35 social support was assessed with the Multidimensional Scale of Perceived Social Support 36 or the Survey of Children’s Social Support, 37 and reasons for staying alive were assessed with the Reasons for Living Inventory 38 or the Reasons for Living Inventory for Adolescents. 39 Family climate was assessed using the child-reported Family Assessment of Cohesion Evaluation Scale. 40 In all participants, child maltreatment was assessed using the Abuse Dimensions Inventory 41 and the Childhood Trauma Questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…30,31 For those 18 years and older vs those younger than 18 years, impulsivity was assessed with the Barratt Impulsivity Scale or the impulsivity subscale of the Conners’ Teacher Rating Scale, 32,33 negative life events in the previous 12 months were assessed with the shortened version of the Social Readjustment Rating Scale or the Life Events Checklist, 34,35 social support was assessed with the Multidimensional Scale of Perceived Social Support 36 or the Survey of Children’s Social Support, 37 and reasons for staying alive were assessed with the Reasons for Living Inventory 38 or the Reasons for Living Inventory for Adolescents. 39 Family climate was assessed using the child-reported Family Assessment of Cohesion Evaluation Scale. 40 In all participants, child maltreatment was assessed using the Abuse Dimensions Inventory 41 and the Childhood Trauma Questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The 7-item Family Alliance scale of the RFL-A was used to assess the connection/cohesiveness of the family (Osman et al, 1998). Family alliance was explored as a protective factor since familial discord, low adaptability, and low support have been associated with adolescent suicidal behavior even after controlling for other known risk factors (Brent, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Family alliance was explored as a protective factor since familial discord, low adaptability, and low support have been associated with adolescent suicidal behavior even after controlling for other known risk factors (Brent, 1995). This specific scale of the RFL-A was used to measure family alliance since other studies have shown an association with this scale and suicidal behavior (Gutierrez, Osman, Kopper, & Barrios, 2000; Lee, 2011; Osman et al, 1998). Items include, My family cares about the way I feel and I enjoy being with my family .…”
Section: Methodsmentioning
confidence: 99%
“…The BHS consists of 20 true-false items pertaining to future outlook [20]. The MDI is a short questionnaire consisting of 12 questions.…”
Section: Methodsmentioning
confidence: 99%